2013
DOI: 10.1039/c3tc31810a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential for high thermoelectric efficiency of silver selenide

Abstract: Measurements and modeling of electronic transport properties of n-type Ag 2+x Se suggest that this material could have a thermoelectric figure of merit zT greater than 1 at 300 K and above. The exceptional performance can be traced to the exceptionally high mobility, higher than other optimized thermoelectric materials. Although zT decreases at high temperature because of a transition to a phase with high carrier concentration, our model indicates that reducing the carrier concentration will lead to high therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
140
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 18 publications
20
140
3
Order By: Relevance
“…In the superionic phase, cations exhibit liquid-like diffusivity [3,4] and this disordered nature typically results in a very low lattice thermal conductivity (<1 W m −1 K −1 ). Many of the superionic compounds, particularly those that are also good electric conductors, indeed show promising thermoelectric properties as exemplified by Cu 2 Se [1,5], Cu 2 S [6,7], Ag 2 Se [8,9], and Zn 4 Sb 3 [10]. Cation movement is seen to be suppressed with the addition of lithium.…”
mentioning
confidence: 89%
“…In the superionic phase, cations exhibit liquid-like diffusivity [3,4] and this disordered nature typically results in a very low lattice thermal conductivity (<1 W m −1 K −1 ). Many of the superionic compounds, particularly those that are also good electric conductors, indeed show promising thermoelectric properties as exemplified by Cu 2 Se [1,5], Cu 2 S [6,7], Ag 2 Se [8,9], and Zn 4 Sb 3 [10]. Cation movement is seen to be suppressed with the addition of lithium.…”
mentioning
confidence: 89%
“…A maximum zT of 0.96 at 300 K is reported only by Ferhat and Nagao. 14 The zT values are much less than the unity in both Ag-rich and Se-rich samples by Lee et al 15 However, the zT around 1.0 in Ag 2 Se is recently predicted again by Day et al 17 using single parabolic band model calculations although it is not realized in their Ag-rich Ag 2 Se samples because the optimum carrier concentration is not reached by the excessive Ag atoms. Thus, the TE performance in Ag 2 Se is still an open question and requires further investigations.…”
mentioning
confidence: 93%
“…43,44 Binary silver chalcogenides have also been tested as thermoelectric materials, showing values of the thermoelectric figure of merit (ZT) close to unity in some cases. [45][46][47][48][49] In the context of thermoelectrics, Xiao et al have reported higher ZT values for ternary Ag 4 SeS alloyed NPs, compared to the binary Ag 2 Se NPs. 50 Other materials in the research spotlight are CuAgSe, AgSbSe 2 and AgBiSe 2 systems, which are currently emerging as promising thermoelectric materials with enhanced ionic and electronic mobilities and ultra-low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%